A study of reverse logistics flow management in vehicle battery industries in the midwest of the state of São Paulo (Brazil) - Hojas Baenas, Jovita Mercedes [UNESP]; de Castro, Rosani [UNESP]; Gomes Battistelle, Rosane Aparecida [UNESP]; Gobbo Junior, Jose Alcides [UNESP] (Elsevier B.V., 2011)
Having the objective of minimizing costs and improving their image in the consumer and export market, car battery industries began to seek environmental alternatives geared towards sustainable development. Reverse logistics flow represents an unprecedented tool for the economic and operational development of company activities, as well as a differential in the search for competitive advantages through environmentally correct practices. The aim of this paper is to describe the reverse logistics chain adopted by automotive battery industries in the midwest of the state of São Paulo, proposing a reverse logistics framework for small manufacturers that creates actions aimed at not harming the environment. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Car batteries; Logistics flows; Recycling; Environment